Identification of 'Wasteful Commuting' using Search Theory - Jos Van Ommeren; Willemijn Van der Straaten (Tinbergen Institute, 2005)
In this paper, we employ search theory as a micro-economic foundation for the wasteful commuting hypothesis. It is argued that the commute of the self-employed is the result of a search process for vacant workplaces, whereas employees search for vacant jobs through space. Because the arrival rate of workplaces is much higher than the arrival rate of jobs, the self-employed essentially may minimise the commute, whereas employees accept jobs with a longer commute. In the empirical analysis, the extent of the `wasteful commuting' is identified by estimating the difference in the commute of employees and self-employed individuals with fixed workplaces. Our estimates indicate that about 40 to 50% of the observed commute may be considered `wasteful' due to job search imperfections. We reject alternative hypotheses why the self-employed have a shorter commute (self-selection of not working from home, different residence locations). In line with the theoretical model, the excess commute is shown to be less in areas with a higher urban density.
Keywords: R20; J64; 330; wasteful commuting; search; mobility; self-employed